On the Origins of Perceptions: Student Perceptions of Active Learning and Their Implications for Educational Reform. Issue 4 (1st October 2016) - Istas, Kathryn; Paolo, Anthony M.; Berardo, Benito A.; Bonaminio, Giulia; Fontes, Joseph D.; Walling, Anne; Davis, Nancy; Cianciolo, Anna T.; Englander, Robert; Koehler, Jeanne L.; Lomis, Kimberly D.
ABSTRACT: This Conversation Starters article presents a selected research abstract from the 2016 Association of American Medical Colleges Central Region Group on Educational Affairs annual spring meeting. The abstract is paired with the integrative commentary of three experts who shared their thoughts stimulated by the study. These thoughts highlight the value of exploring what drives student perceptions of active learning in order to reform medical education.